Development and evaluation of a low-cost precision seeding control system for a corn drill - Yin, Xiang; Noguchi, Noboru; Yang, Tengxiang; Jin, Chengqian (International Journal of Agricultural and Biological Engineering, 2018)
Precision seeding requires that the corn drill drop seeds into the soil by a specific in-row spacing while its travelling speed fluctuates due to unevenness of the field ground. This paper presents a low-cost precision seeding control system for a conventional corn drill with mechanical metering devices of finger-pickup type. A median filtering method was implemented in the control system to process measurements from a rotary encoder in order to acquire stable values of the corn drill travelling speed. The metering unit was driven by an electric motor controlled by the metering ECU according to the actual travelling speed and the desired in-row spacing in real-time. A user interface was programmed to communicate with ECUs for configuring parameters and displaying operating information during working. The newly-developed precision seeding control system was first calibrated in terms of speed measurement and control for two ECUs. Experiments were conducted on a seeding test platform in the laboratory for evaluating its accuracy in dropping seeds by giving different in-row spacing under different travelling speeds of the conveyor sticky belt. Results showed that the average spacing error was less than 2 cm and the maximum RMS error was 0.78 cm for all spacing values including 25 cm, 30 cm and 35 cm under the travelling speed of 1.0-8.0 km/h. These indicated that the low-cost precision seeding control system worked in a both accurate and stable way. Keywords: precision seeding, corn drill, control system, travelling speed, in-row spacing DOI: 10.25165/j.ijabe.20181105.3369 Citation: Yin X, Noguchi N, Yang T X, Jin C Q. Development and evaluation of a low-cost precision seeding control system for a corn drill. Int J Agric & Biol Eng, 2018; 11(5): 95–99.